Evaluation of anticonvulsant, antimicrobial and hemolytic activity of Aitchisonia rosea (Bangladesh Journal of Pharmacology, 2015)
The purpose of this study was to evaluate the anticonvulsant, antimicrobial and hemolytic effect of Aitchisonia rosea. The anticonvulsant effect was studied at doses 400 and 800 mg/kg against pentylenetetrazole, strychnine and picrotoxin-induced seizures in albino mice. The antimicrobial assay was conducted by disc diffusion method and minimum inhibitory concentration. Hemolytic effect was analyzed by reported method. Phenolic compounds present in the n-butanol fraction of the plant were estimated by HPLC. The plant showed maximum response against drug-induced convulsions and provided protection to animals at both doses. It also showed maximum zone of inhibition and highly significant MIC against all bacterial and fungal strains. The plant protected the RBCs from hemolysis. The highest amount of phenolics found was caffeic acid (7.5 ± 0.04).